AN ANALYSIS OF GRAMMATICAL ERRORS ON NARRATIVE WRITING COMMITTED BY THE NINTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Budiarta, L. G. R.; Suputra, P. E. D.; Widiasmara, I. K. (International Journal of Language and Literature, 2018)
Writing is a difficult skill in English; most of English for Foreign Language students tend to make errors in writing. In assisting the learners to successfully acquire writing skill, an analysis of errors is necessary to be conducted. This study aims at identifying the types of grammatical errors on students’ narrative writings and analyzing the causing factors contributing to the students’ errors. Descriptive qualitative design was applied in this study. The subjects of the study were the ninth grade students of SMP Negeri 1 Sukawati. The data were collected from students’ narrative writings, questionnaires, andinterviews. In analyzing the data, this study applied the theory from Dulay et al. (1982) in identifying the types of errors and for analyzing the contributing factors of the errors this study used Brown’s (2000) theory. The result of the data analysis showed that the most frequent type of grammatical errors committed wasmisformation error (46.50%), followed by omission error (35.56%), addition error (14.74%), and the least one was misordering error (3.19%). Moreover, the sources of errors were dominated by intralingual transfer (35.33%), followed by interlingual transfer (34.50%), and context of learning (30.15%). Related to this findings, this study had similar result with Hamid & Qayyimah’s (2014) and Ma’mun’s (2016) researcheswhich also found misformation and intralingual transfer as the biggest contributing factors to the errors. Therefore, this present study suggests that the teachers have to find a better way in teaching and learning process of writing and students have to practice more vocabulary especially regarding the forms of verbs, so it can minimize the grammatical errors that occur. Keywords:error analysis, grammatical errors, sources of errors, narrative text